ANALISIS KESULITAN BELAJAR MAHASISWA PADA MATA KULIAH KAPITA SELEKTA MATEMATIKA SEKOLAH MENENGAH - Ade Kumalasari; Sugiman Sugiman (Jurnal Riset Pendidikan Matematika, 2015)
Penelitian ini bertujuan untuk mendeskripsikan letak dan jenis kesulitan belajar matematika mahasiswa pendidikan matematika. Penelitian ini adalah penelitian campuran dengan pendekatan kuantitatif dan kualitatif. Subjek penelitian ini adalah mahasiswa pendidikan matematika di Universitas Jambi yang mengalami kesulitan belajar matematika pada mata kuliah Kapita Selekta Matematika Sekolah Menengah II. Instrumen yang digunakan berupa tes diagnostik dan pedoman wawancara. Letak kesulitan belajar matematika dilihat berdasarkan kesalahan/kesulitan mahasiswa dalam menyelesaikan tes diagnostik. Mahasiswa yang dikategorikan mengalami kesulitan diwawan-carai untuk memperoleh konfirmasi mengenai jenis kesulitan belajar matematika. Hasil penelitian menunjukkan bahwa kesulitan belajar matematikan mahasiswa terletak pada pengetahuan faktual 12,2%, pengetahuan konseptual 19,7%, pengetahuan prosedural 20,7%, dan pengetahuan metakognitif 47,4%.  Jenis kesulitan belajar matematika yang dialami peserta didik adalah kesulitan mengingat fakta 1,9%, kesulitan mengingat konsep 13,1%, kesulitan memahami fakta 8%, kesulitan memahami konsep 5,2%, kesulitan menerapkan konsep 0,9%, kesulitan menerapkan prosedur 0,9%, kesulitan menganalisis prosedur 7%, kesulitan mengevaluasi konsep 0,5%, kesulitan mengevaluasi prosedur 8,9%, kesulitan mengomunikasikan metakognitif 47,4%, kesulitan meneliti fakta 2,3%, dan kesulitan meneliti prosedur 3,8%. Kata Kunci: analisis kesulitan belajar, kapita selekta matematika sekolah menengah   AN ANALYSIS ON LEARNING DIFFICULTIES OF STUDENTS ON CAPITA SELECTA MATHEMATICS SUBJECT OF SECONDARY SCHOOL Abstract This research aims to describe the mathematics learning difficulty locations and the mathematics learning difficulties types faced by mathematics education students. This research is a mix method research study which used a quantitative and a qualitative approach. This research’s subjects were students of mathematics education in Jambi University who had learning difficulties on Capita Selecta of Secondary School II subject. The instruments used here were in diagnostic test and interview guide. The locations of learning difficulties viewed based on students’ mistakes/difficulties in completing the diagnostic test. These students categorized as students who were experiencing learning difficulties were interviewed to obtain confirmation regarding the mathematics learning difficulties types. The research result suggests that mathematics learning difficulty locations faced by the research subjects are factual knowledge 12.2%, conceptual knowledge 19.7%, procedural knowledge 20.7%, and metacognitive difficulties 47.4%. The mathematics learning difficulties types faced by the research subjects are fact remembering difficulty 1.9%, concept remembering difficulty 13.1%, fact understanding difficulty 8%, concept understanding difficulty 5.2%, concept applying difficulty 0.9%, procedure applying difficulty 0.9%, procedure analyzing difficulty 7%, concept  evaluating difficulty 0.5%, procedure evaluating difficulty 8.9%, written metakognitive communicating difficulty 47.4%, fact observing difficulty 2.3%, and procedure observing difficulty 3.8%. Keywords: analysis on learning difficulties, capita selecta mathematics of secondary schooll